Melecio Galván y su espacio significativo : las líneas de la memoria, 1968-1982 - González Cruz Manjarrez, Maricela (Instituto de Investigaciones Estéticas, Universidad Nacional Autónoma de México : Bonilla Artigas Editores, 2018)
Between 1977 and 1981, Melecio Galván (1945-1982) was part of the Mira Group, a Mexican collective of the post 68 generation in whose practices political work, ethics and aesthetics, activism and art coexisted. The selection of drawings that comprise this book is part of Militarismo y represión" (Militarism and repression, 1980), the most representative series of the artist. It shows the close implication of a rigorous drawing technique with an acute political sensitivity around the systemic violence that survives in Mexico to this day.